Effect of IAA on in vitro growth and colonization of Nostoc in plant roots - Hussain, Anwar; Shah, Syed T.; Rahman, Hazir; Irshad, Muhammad; Iqbal, Amjad (Frontiers in Plant Science, 2015)
Nostoc is widely known for its ability to fix atmospheric nitrogen and the establishment of symbiotic relationship with a wide range of plants from various taxonomic groups. Several strains of Nostoc produce phytohormones that promote growth of its plant partners. Nostoc OS-1 was therefore selected for study because of the presence of putative ipdC gene that encodes a key enzyme to produce Indole-3-acetic acid (IAA). The results indicated that both cellular and released IAA was found high with increasing incubation time and reached to a peak value (i.e., 21 pmol mg-1ch-a) on the third week as determined by UPLC-ESI-MS/MS. Also the Nostoc OS-1 strain efficiently colonized the roots and promoted the growth of rice as well as wheat under axenic conditions and induced ipdC gene that suggested the possible involvement of IAA in these phenotypes. To confirm the impact of IAA on root colonization efficiency and plant promoting phenotypes of Nostoc OS-1, an ipdC knockout mutant was generated by homologous recombinant method. The amount of releasing IAA, in vitro growth, root colonization, and plant promoting efficiency of the ipdC knockout mutant was observed significantly lower than wild type strain under axenic conditions. Importantly, these phenotypes were restored to wild-type levels when the ipdC knockout mutant was complemented with wild type ipdC gene. These results together suggested that ipdC and/or synthesized IAA of Nostoc OS-1 is required for its efficient root colonization and plant promoting activity.